A protocol for developing, disseminating, and implementing a core outcome set for stress urinary incontinence. Issue 37 (September 2019) - Rada, Maria-Patricia; Pergialiotis, Vasilios; Betschart, Cornelia; Falconi, Gabriele; Haddad, Jorge Milhem; Doumouchtsis, Stergios K.
Abstract: Introduction: Randomized trials evaluating interventions for stress urinary incontinence (SUI) have been using variable outcome measures, reporting a variety of outcomes. Alongside this variation across studies, outcome-reporting flaws contribute to a limited use of research to inform clinical practice. The development and use of core outcome sets (COSs) in future trials would ensure that outcomes important to different stakeholders and primarily women with SUI are reported more consistently and comprehensively. Methods: An international steering group including healthcare professionals, researchers, and women with urinary incontinence will guide the development of this COS. Potential outcomes will be identified through comprehensive literature reviews. These outcomes will be entered into an international, multiperspective online Delphi survey. All key stakeholders, including healthcare professionals, researchers, and women with urinary incontinence, will be invited to participate. The modified Delphi method encourages stakeholder group convergence toward collective agreement, also referred as consensus, core outcomes. Discussion: Dissemination and implementation of the resulting COS within an international context will be promoted and reviewed. Embedding the COS for SUI within future clinical trials, systematic reviews and clinical practice guidelines could make a significant contribution to advancing the value of research in informing clinical practice, enhancing patient care and improving outcomes. The infrastructure created by developing a COS for SUI could be leveraged in other settings, for example, selecting research priorities and clinical practice guideline development. Abstract : Supplemental Digital Content is available in the text